Treatment for asymptomatic vaginal candidiasis to reduce preterm birth: a systematic review - Abdel-Fattah, Hanah; Aljuwaiser, Sameera; Monro, Carol; Mostafa, Alyaa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Vaginal candidiasis, a prevalent fungal infection in women caused by the overgrowth of Candida species, primarily Candida albicans, often triggers a hyperimmune response. While it is rarely life-threatening, it can be uncomfortable, posing risks to both pregnant mothers and their unborn children, thus affecting quality of life. This systematic review aimed to determine whether treating asymptomatic vaginal candidiasis during pregnancy reduces the incidence of preterm birth. Literature search was conducted across four electronic databases finds randomised controlled trials (RCTs) comparing the treatment of vaginal candidiasis (clotrimazole) with usual care (no-treatment). The search was updated in August 2024, with no language restrictions. Participants were pregnant women between 12 and 20 weeks of gestation. The primary outcome measured was the rate of preterm birth, while secondary outcomes included adverse pregnancy events such as premature rupture of membranes, perinatal death, low birth weight, and stillbirth. Data analysis utilized review manager (RevMan) software. Three RCTs involving 3,868 pregnant women were included, with 1,942 in the clotrimazole group and 1,926 in the usual care group. The primary outcome revealed spontaneous preterm birth rates of 2% in the treatment group compared to 6.3% in the usual care group. Meta-analysis indicated a statistically significant effect favouring treatment, with a pooled effect size of -0.05 (95% CI -0.09, -0.01). Treating asymptomatic candidiasis in early pregnancy appears to reduce preterm birth risk. However, results should be interpreted cautiously due to the limited number of studies. Further well-designed trials are needed to optimise treatment strategies and assess their impact on neonatal outcomes.